2021
DOI: 10.1097/cnq.0000000000000350
|View full text |Cite
|
Sign up to set email alerts
|

Patient Perspectives of Sickle Cell Management in the Emergency Department

Abstract: Sickle cell disease (SCD) is a common genetic blood disorder predominantly affecting African Americans in the United States. The objective of this study was to use a multimethods approach to describe how patients with SCD in North Carolina perceive the care they receive in emergency departments (EDs). Fourteen participants completed an interview (n = 10) or 2 focus groups (n = 2 per focus group) and 51 completed surveys. Sixty percent of participants with pain attack “very much” or “quite a bit” avoided going … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 44 publications
2
10
0
Order By: Relevance
“…Nearly two‐thirds of clinicians cited patient concern about side effects and lack of knowledge about a medication as potential barriers, and these two concerns were the most frequently cited by patients. This finding aligns with concerns identified in previous studies regarding pain management in patients with SCD [32–36]. Clinicians should be aware that lack of education regarding medication mechanism, utility, and potential side effects are potential barriers to patient use, and plan for thorough, patient‐facing conversations to assuage these fears.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Nearly two‐thirds of clinicians cited patient concern about side effects and lack of knowledge about a medication as potential barriers, and these two concerns were the most frequently cited by patients. This finding aligns with concerns identified in previous studies regarding pain management in patients with SCD [32–36]. Clinicians should be aware that lack of education regarding medication mechanism, utility, and potential side effects are potential barriers to patient use, and plan for thorough, patient‐facing conversations to assuage these fears.…”
Section: Discussionsupporting
confidence: 85%
“…We did not identify prior reports of patient or clinician perspectives specific to management of NP in SCD. Several studies have collected perspectives on general pain management or management of acute pain in SCD, highlighting common themes such as the importance of trust in the clinician-patient relationship, frequent underestimation of pain, clinician concerns about adherence and drug-seeking behaviors, stigma associated with certain medications, and concerns about side effects and risk of addiction if patients are prescribed opioids [32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants affirmed previously described challenges with ED care for people with SCD, including lack of familiarity with clinical teams, care delays, ED clinicians' limited SCD knowledge, and clinician bias. [18][19][20] In the ED, self-advocacy is an essential skill for being a "good patient." Although no participants in this study explicitly identified racism as a cause for unfair or inadequate treatment, most young adults with SCD in the United States and in this study are Black.…”
Section: Discussionmentioning
confidence: 99%
“…The primary trigger that forces SCD patients to seek urgent medical care is the onset of acute severe pain that cannot be treated at home with the current medications that are used daily. Although patients with SCD do not seek out pain management providers in the community, there is still a perception that individuals with the disease are “drug abusers or drug-seeking” (Crego et al, 2021). Individuals with SCD are aware of the perception, but the pain is so intense and debilitating that they have no other recourse but to enter the health care system for relief.…”
mentioning
confidence: 99%